Phase IB Study of Induction Chemotherapy With XELOX, Followed by Radiation Therapy, Carboplatin, and Everolimus in Patients With Locally Advanced Esophageal Cancer. (April 2019) - Saba, Nabil F.; Force, Seth; Staley, Charley; Fernandez, Felix; Willingham, Field; Pickens, Allan; Cardona, Kenneth; Chen, Zhengjia; Goff, Laura; Cardin, Dana; Lambright, Eric; Nesbitt, Jon; et al.
Abstract : Purpose: Preclinical studies have shown synergy between everolimus, an mTOR inhibitor, radiation, and platinum agents. We conducted a phase IB trial to determine the recommended phase II dose of everolimus with carboplatin and radiation. Materials and Methods: Patients with stage II/III esophageal cancer were enrolled. Following 2 cycles of Capecitabine/Oxaliplatin (XELOX), patients with no disease progression, received 50.4 Gy in 28 fractions and concurrent weekly carboplatin (area under the curve=2), with escalating doses of everolimus. A standard 3+3 dose escalation design was used. Results: Nineteen patients were enrolled. Two patients were screen failures and 4 were removed due to poor tolerance to XELOX (n=2) or disease progression (n=2). All treated patients had adenocarcinoma. Median age was 58 (44 to 71 y) and 85% were male patients. One patient at dose level 1 was replaced due to ongoing anxiety. One of 6 patients had a dose-limiting toxicity of bowel ischemia that was fatal. At dose level 2, two of 6 patients had a dose-limiting toxicity (fever with neutropenia and nausea). The recommended phase II dose of everolimus was 2.5 mg QOD. Grade ≥3 toxicities included lymphopenia (11%), nausea (10%), low white blood cell (8.0%) vomiting (5.5%), decreased neutrophils (4.0%). All patients achieved an R0 resection with a pathologic response rate of 40% and a pathologic complete response (ypCR) rate of 23%. The 2-year progression-free survival and overall survival were 50% and 49.6%, respectively. Conclusions: The recommended phase II dose of everolimus with concurrent weekly carboplatin and radiation is 2.5 mg QOD.